Peran Akuntansi Forensik dan Audit Investigasi Dalam Pengungkapan Kasus Fraud - Gita Lamarwati Kesuma Putri; Deviana sari (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to examine the influence of the role of Forensic Accountants and Investigative Audits in detecting fraudulent activities. In addition, the study is expected to provide benefits in both theoretical and practical aspects. Theoretically, this research can serve as an additional reference for studies discussing the role of Forensic Accountants in uncovering fraud cases, including corruption. Practically, the findings of this study are expected to contribute insights for the government in formulating solutions to address fraud and corruption, as well as to provide input for authorities in developing policies for corruption eradication in Indonesia. The research method employed is a qualitative approach combined with a literature review. The results indicate that forensic accounting and investigative auditing play a crucial role in detecting and controlling fraud. Forensic Accountants have a very important role in uncovering fraud cases, as forensic accounting is capable of identifying early clues or indications of fraud that may lead to fraudulent activities within an organization or company. The primary task of a Forensic Accountant after fraud has occurred is to detect the fraud itself. This process is part of an investigative audit that focuses on fraud detection. Fraud detection can be carried out using two methods, namely Critical Point Auditing (CPA) and Job Sensitivity Analysis (JSA). An investigative audit is a type of examination conducted based on strong reasons to perform an investigation. In uncovering fraud cases within institutions or agencies, forensic accounting applies investigative auditing to criminal acts. Investigative audits aim to identify and disclose fraud or criminal activities; therefore, the approaches, procedures, and techniques used in this type of audit differ from those used in financial audits, performance audits, and other special-purpose audits.